High-temperature oxidation behavior of iron-chromium-aluminum alloys - Sadique, S.E.; Mollah, A.H.; Islam, M.S.; Ali, M.M. (Springer Nature, 2000)
The detailed oxidation behavior of Fe-10Cr alloys, containing aluminum in the range of 2-8% by weight, was studied in pure oxygen at 1 atm pressure. The investigations were performed over the temperature range 950-1050 °C under cyclic conditions (3-hr cycles) in each case. The cyclic-oxidation resistance, as measured by the specific weight-gain values, was observed to progressively improve with increasing aluminum content in the alloy. For a particular aluminum content, however, the oxidation resistance decreased with increasing temperature. Following the initial transient-oxidation period, a healing layer of chromia was established on the four alloys. The lower-aluminum alloys (2-4% Al) were observed to end up with Fe-rich oxide scales under the experimental conditions at all temperatures, whereas those containing aluminum in the range of 6-8% formed α-Al2O3 scales.